Colchicine Acutely Suppresses Local Cardiac Production of Inflammatory Cytokines in Patients With an Acute Coronary Syndrome - Martínez, Gonzalo J (J Am Heart Assoc, 2015)
BACKGROUND: Interleukin (IL)-1β, IL-18, and downstream IL-6 are key inflammatory cytokines in the pathogenesis of coronary artery disease. Colchicine is believed to block the NLRP3 inflammasome, a cytosolic complex responsible for the production of IL-1β and IL-18. In vivo effects of colchicine on cardiac cytokine release have not been previously studied. This study aimed to (1) assess the local cardiac production of inflammatory cytokines in patients with acute coronary syndromes (ACS), stable coronary artery disease and in controls; and (2) determine whether acute administration of colchicine inhibits their production. METHODS AND RESULTS: Forty ACS patients, 33 with stable coronary artery disease, and 10 controls, were included. ACS and stable coronary artery disease patients were randomized to oral colchicine treatment (1 mg followed by 0.5 mg 1 hour later) or no colchicine, 6 to 24 hours prior to cardiac catheterization. Blood samples from the coronary sinus, aortic root (arterial), and lower right atrium (venous) were collected and tested for IL-1β, IL-18, and IL-6 using ELISA. In ACS patients, coronary sinus levels of IL-1β, IL-18, and IL-6 were significantly higher than arterial and venous levels (P=0.017, <0.001 and <0.001, respectively). Transcoronary (coronary sinus-arterial) gradients for IL-1β, IL-18, and IL-6 were highest in ACS patients and lowest in controls (P=0.077, 0.033, and 0.014, respectively). Colchicine administration significantly reduced transcoronary gradients of all 3 cytokines in ACS patients by 40% to 88% (P=0.028, 0.032, and 0.032, for IL-1β, IL-18, and IL-6, respectively). CONCLUSIONS: ACS patients exhibit increased local cardiac production of inflammatory cytokines. Short-term colchicine administration rapidly and significantly reduces levels of these cytokines.